Effect of kinetic mechanisms of lower limbs on torso motion in baseball batting for different ball speeds - Takagi, T.; Fujji, N.; Koike, S.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
It is known that baseball batters adjust movements of the torso, and lower and upper limbs to hit the ball when ball course and speed vary. However, few studies investigated the effect of kinetic mechanisms of lower limbs on torso motion for different ball speeds. Therefore, the purpose of this study was to investigate effects of kinetic mechanisms of lower limbs on torso motion in baseball batting for different ball speeds.